Does Spinal Block Through Tattooed Skin Cause Histological Changes in Nervous Tissue and Meninges? An Experimental Model in Rabbits. Issue 3 (September 2016) - Ferraz, I.L.; Barros, G.A.; Ferreira Neto, P.G.; Solanki, D.; Marques, M.A.; Machado, V.M.; Cabral, L.W.; Lima, R.M.; Vianna, P.T.; Navarro, L.H.; Ganen, E.M.
Abstract : ( Reg Anesth Pain Med. 2015;40(5):533–538) As tattoos continue to become a more pervasive cultural trend, it is increasingly likely for anesthesiologists to encounter patients with tattoos covering their lumbar and sacral area. Although there are currently no reports of complications from placing a needle through tattooed skin, there are also insufficient data to determine whether it is completely safe. Concerns are that ink fragments, which may contain carcinogenic amides, can be accidentally deposited in the subarachnoid space, leading to arachnoiditis. The authors of this study investigated whether placing a 22-G spinal needle through tattooed skin could result in changes to the spinal cord and meninges or if fragments of ink could become trapped in the needle bore.